Pengembangan Instrumen Penilaian Akhlak Mulia Berbasis Al-Qur’an - Imam Shofwan (Madaniyah, 2018)
Noble morals become an important aspect of daily life, whatever social status noble morals should always be attached to, both in their position as individuals, family members, community members and as a nation. Cultivation of noble morals should start from the family, primary and secondary schools is a strategic step to overcome moral problems amid the complexities of life in the community. Besides noble character can be a barometer of someone's piety before God and others, therefore someone who has noble character will get the title from the community as pious people. The purpose of character education is that students have the ability and thinking skills, become useful members of society and have commendable abilities. In order to realize national education, character education is integrated with a number of relevant subjects with the aim that students are able to use knowledge, study and internalize social values ​​and skills to develop noble morals that are manifested in everyday behavior. Judgment of noble character is a way of character building.